2005
DOI: 10.1088/0960-1317/15/9/s04
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined silicon structures for free-convection PEM fuel cells

Abstract: This paper presents details on the design, fabrication, testing and modeling of micromachined gas diffusion media (GDM) for micro proton exchange membrane (PEM) fuel cell applications. Two-tiered mesh structures were thru-etched into silicon wafers and subsequently assembled with membrane electrode assemblies (MEAs) and tested with hydrogen fuel and ambient air as the oxidizer. These silicon structures doubled as gas diffusion layers and supports for thermally evaporated gold current collection layers that mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…A similar sort of experiment was also performed by Hottinen et al [48] using titanium sinter material and their investigation illustrated the applicability of titanium sinter as a GDM in free-breathing PEM fuel cells. Micromachined silicon has also been used as GDM for microPEM fuel cell applications tested with hydrogen/air [49]. The technique of incorporating sintered stainless steel fibre felt was implemented by Yi et al [50] and they inferred that the compressive modulus and ductility of GDL were improved.…”
Section: Novel Gas Diffusion Mediummentioning
confidence: 99%
“…A similar sort of experiment was also performed by Hottinen et al [48] using titanium sinter material and their investigation illustrated the applicability of titanium sinter as a GDM in free-breathing PEM fuel cells. Micromachined silicon has also been used as GDM for microPEM fuel cell applications tested with hydrogen/air [49]. The technique of incorporating sintered stainless steel fibre felt was implemented by Yi et al [50] and they inferred that the compressive modulus and ductility of GDL were improved.…”
Section: Novel Gas Diffusion Mediummentioning
confidence: 99%
“…Lee et al (2002) reported arrays of hydrogen-air PEM fuel cells formed on silicon substrates, wherein a reconfigurable cathode electrode enabled scaling of either current or voltage. An additional configuration has been reported to form the porous silicon or silicon dioxide catalyst/electrode support on the same side of the silicon wafer Meyers and Maynard (2002) 63 Hydrogen PEM, 258C Modroukas et al (2005) 130 Hydrogen PEM, 388C Yeom et al (2005) 35 Hydrogen PEM, 208C Yu et al (2003) 195 Hydrogen PEM, 258C Kelley et al (2002) 90 0.5 M CH 3 OH, DMFC, 708C Motokawa et al (2004) 0.78 2 M CH 3 OH, DMFC, 258C Yen et al (2003) 40 4 M CH 3 OH, DMFC, 258C Wosniak (2004) 0.3 6 M CH 3 OH, DMFC, 258C…”
Section: Miniaturization Methodsmentioning
confidence: 99%
“…• C. Modroukas et al [12,13] studied the utilization of a passive water control system based on hydrophilic material that enhances water removal from the cell and thereby increased the cell performance. O'Hayre et al [14] studied in the temperatures ranging from 10 to 80…”
Section: Introductionmentioning
confidence: 99%